2005
DOI: 10.1007/s11886-005-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic valvular disease: Who benefits from surgery?

Abstract: Routine physical examination and noninvasive imaging frequently lead to the diagnosis of valvular heart disease in asymptomatic patients. The decision to proceed to surgical repair or replacement is based on an informed evaluation of the risks of surgery versus those encountered with a nonoperative course. In determining whether symptoms are present, stress testing may be helpful, as many patients with significant valvular lesions have a tendency to limit their daily physical exertion to levels that do not pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…[27][28][29][30] In humans, conventional echo-Doppler examination therefore has much improved the definition of high-risk patients that might benefit from early medical or surgical treatment. [27][28][29][30][31][32][33] For example, ACEI therapy has been shown to have some beneficial effects on MR in asymptomatic human patients with moderate to severe MR. 34,35 Similarly, the recent prospective study by Atkins et al 9 demonstrated a benefit (ie, increased time to CHF-all-cause death and delayed onset of CHF) of early treatment with enalapril. Although in the latter study MR was not assessed using a Doppler method, we can hypothesize that all the recruited dogs had severe (although compensated) MR, because left atrial enlargement on M-mode or 2D echocardiography was one of the inclusion criteria.…”
Section: Discussionmentioning
confidence: 93%
“…[27][28][29][30] In humans, conventional echo-Doppler examination therefore has much improved the definition of high-risk patients that might benefit from early medical or surgical treatment. [27][28][29][30][31][32][33] For example, ACEI therapy has been shown to have some beneficial effects on MR in asymptomatic human patients with moderate to severe MR. 34,35 Similarly, the recent prospective study by Atkins et al 9 demonstrated a benefit (ie, increased time to CHF-all-cause death and delayed onset of CHF) of early treatment with enalapril. Although in the latter study MR was not assessed using a Doppler method, we can hypothesize that all the recruited dogs had severe (although compensated) MR, because left atrial enlargement on M-mode or 2D echocardiography was one of the inclusion criteria.…”
Section: Discussionmentioning
confidence: 93%
“…In the context of mild and moderate AR, there is only very limited data on the long-term progression and follow-up. 3,4 The current guidelines for surveillance echocardiography recommends appropriate periodic testing, every 2-3 years, for monitoring Stage B progressive AR patients. 5,6 Chronic kidney disease (CKD) is a significant comorbidity for most major cardiovascular diseases 7,8 ; it is associated with significant mortality and morbidity in patients with valvular heart disease or those undergoing valvular procedures, especially for calcified valvular disease (such as aortic stenosis or mitral stenosis).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the clinical features progressing to heart failure or cardiovascular outcome have not been elucidated. In the context of mild and moderate AR, there is only very limited data on the long‐term progression and follow‐up 3,4 . The current guidelines for surveillance echocardiography recommends appropriate periodic testing, every 2–3 years, for monitoring Stage B progressive AR patients 5,6 …”
Section: Introductionmentioning
confidence: 99%